Formulation and Evaluation of a Facial Mask Prepared from Green Tea (Camellia sinensis) Waste and Honey as a Cosmetic for Acne-Prone Skin - Utami, Marsha Dwicahya; Ambarwati, Neneng Siti Silfi; Jubaedah, Lilis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Acne is a skin condition influenced by excessive sebum production, clogged pores, and the growth of Cutibacterium acnes bacteria. Green tea dregs retain catechins, flavonoids, and tannins compounds with potential antioxidant and antibacterial properties while honey possesses humectant, anti-inflammatory, and antimicrobial qualities, making both suitable candidates for development as natural cosmetic active ingredients. This study aimed to formulate a paste-type face mask using green tea dregs and honey, evaluate the product's physical characteristics, identify the optimal formula, and assess the selected formula's antibacterial activity against Cutibacterium acnes. An experimental laboratory method was employed using four formulas containing varying concentrations of green tea dregs: F0 (0%), F1 (5%), F2 (10%), and F3 (15%). Evaluations included organoleptic properties, pH, viscosity, homogeneity, spreadability, drying time, stability, irritation potential, and antibacterial activity via the disc diffusion method. The results demonstrated that all formulas met the physical quality standards for face masks, exhibiting a pH of 5.4–6.4, viscosity of 12,422–42,582 mPa.s, spreadability of 5.1–5.9 cm, and drying times ranging from 15 minutes 38 seconds to 23 minutes 21 seconds; they were stable during storage, homogeneous, and non-irritating. Based on the physical evaluations, Formula F3 was determined to be the best formulation. Antibacterial testing revealed that Formula F3 produced an inhibition zone diameter of 15.15 mm against Cutibacterium acnes, falling into the